In vitro/vivo assessment of praziquantel nanocrystals: Formulation, characterization, and pharmacokinetics in beagle dogs - Ruyi Yang; Tao Zhang; Jiang Yu; Yan Liu; Yingli Wang; Zhonggui He (Elsevier, 2019)
To investigate the impact of particle size on in vitro/vivo performance of praziquantel (PZQ), nanocrystals (NCs) and microcrystals (MCs) of PZQ were prepared using the methods of wet milling and jet milling, respectively. PZQ NCs and MCs were characterized with dynamic light scattering, laser particle size analyzer, transmission electron microscopy, differential scanning calorimetry, X-ray powder diffraction and fourier transform infrared spectroscopy. The average diameters of PZQ NCs and MCs were 364.4 nm and 3.7 µm, respectively. No change in crystalline form was observed. Dissolution tests were performed in two different media, where the cumulative dissolution and dissolution rate of NCs were significantly improved in comparison with those of MCs and KANGQING® in non-sink condition. Similarly, oral bioavailability of PZQ NCs in beagle dogs was 1.68 (P < 0.05) and 1.83 fold (P < 0.01) higher than that of MCs and KANGQING®. Considering the advantages of in vitro/vivo performance and facile preparation, PZQ NCs may have a great application in the treatment of schistosomiasis. Keywords: Praziquantel, Nanocrystals, Microcrystals, Dissolution, Pharmacokinetics